Thermodynamic Control of Intramolecular Singlet Fission and Exciton Transport in Linear Tetracene Oligomers. Issue 8 (18th January 2023) - Nakamura, Shunta; Sakai, Hayato; Fuki, Masaaki; Ooie, Rikuto; Ishiwari, Fumitaka; Saeki, Akinori; Tkachenko, Nikolai V.; Kobori, Yasuhiro; Hasobe, Taku
Abstract: We newly synthesized a series of homo‐ and hetero‐tetracene (Tc) oligomers to propose a molecular design strategy for the efficient exciton transport in linear oligomers by promoting correlated triplet pair (TT) dissociation and controlling sequential exciton trapping process of individual doubled triplet excitons (T+T) by intramolecular singlet fission. First, entropic gain effects on the number of Tc units are examined by comparing Tc‐homo‐oligomers [(Tc) n : n =2, 4, 6]. Then, a comparison of (Tc) n and Tc‐hetero‐oligomer [TcF3 ‐(Tc)4 ‐TcF3 ] reveals the vibronic coupling effect for entropic gain. Observed entropic effects on the T+T formation indicated that the exciton migration is rationalized by number of possible TT states increased both by increasing the number of Tc units and by the vibronic levels at the terminal TcF3 units. Finally, we successfully observed high‐yield exciton trapping process (trapped triplet yield: Φ TrT =176 %). Abstract : A series of newly synthesized homo‐ and hetero‐tetracene (Tc) oligomers are presented. The molecular design strategy achieves efficient exciton transport in linear tetracene oligomers by promoting correlated triplet pair (TT) dissociation and controlling a sequential exciton trapping process by intramolecular singlet fission.